2018
DOI: 10.1007/s40123-018-0138-6
|View full text |Cite
|
Sign up to set email alerts
|

The Routine Use of Intracameral Antibiotics to Prevent Endophthalmitis After Cataract Surgery: How Good is the Evidence?

Abstract: Post-operative endophthalmitis (POE) following cataract surgery is an uncommon, vision-threatening complication that has been reported to occur at rates of between approximately 0.03% and 0.2%. Prompt diagnosis and treatment of endophthalmitis is critical for minimizing vision loss, but most recent efforts have focused on the prophylactic administration of antibiotics to prevent the development of endophthalmitis. Surgeons from around the world have different topical and intracameral antibiotic usage patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 66 publications
0
29
0
2
Order By: Relevance
“…The most critical steps for minimizing the incidence of visual loss due to endophthalmitis are prompt diagnosis and early treatment. However, most recently all the efforts have been focused on the administration of antibiotics prophylactically so as to prevent the development of endophthalmitis 12 . For prevention of this serious complication many methods have been tried and tested from instillation of 5% povidone iodine in the eye pre-operatively to subconjunctival and intra-cameral antibiotic injections at the end of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The most critical steps for minimizing the incidence of visual loss due to endophthalmitis are prompt diagnosis and early treatment. However, most recently all the efforts have been focused on the administration of antibiotics prophylactically so as to prevent the development of endophthalmitis 12 . For prevention of this serious complication many methods have been tried and tested from instillation of 5% povidone iodine in the eye pre-operatively to subconjunctival and intra-cameral antibiotic injections at the end of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moxifloxacin has a dose-dependent action and achieves an initial aqueous concentration up to 300 times greater than the MIC when injected intracamerally in a dose of 0.5 mg/0.1 mL. [ 20 21 22 ] It maintains its efficacy for a longer duration as compared with cefuroxime.…”
Section: Intraoperative Measuresmentioning
confidence: 99%
“…3,42 Nevertheless, the 2014 American Society of Cataract and Refractive Surgery survey revealed that 90% of surgeons still use topical antibiotics perioperatively, 43 most commonly a fourth-generation fluoroquinolone. 44 More recent debate has centered on the use of IC antibiotics at the time of cataract surgery, with Sharma et al 45 finding only a marginal benefit. The original European Society of Cataract and Refractive Surgeons (ESCRS) study found a 4.92-fold higher rate of endophthalmitis in a group that did not receive IC cefuroxime.…”
Section: Prophylaxismentioning
confidence: 99%
“…48,49 A shortcoming of retrospective studies is the failure to account for improvements in surgical and aseptic technique that occurred over the same time periods. 44 Recently, both moxifloxacin and cefuroxime have demonstrated efficacy at reducing endophthalmitis after phacoemulsification compared to controls. 50 A large analysis of cataract surgeries showed that eyes receiving IC moxifloxacin prophylaxis had significantly reduced endophthalmitis rates, 3-fold lower in manual small-incision cataract surgery (M-SICS) and 6-fold lower in phacoemulsification.…”
Section: Prophylaxismentioning
confidence: 99%